TELAAHAN LOGAM BERAT Pb DAN Cd PADA SEDIMEN DI PERAIRAN BARAT LAUT DUMAI – RIAU - Syahminan Syahminan; Etty Riani; Syaiful Anwar; Rifardi Rifardi (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2015)
This research was conducted in Dumai sea western waters, Riau Province. Dumai marine waters are part of the territorial waters of Riau that relate directly to the Strait of Malacca, and are at Rupat Strait region, and has a high accessibility of the region, both locally and internationally. Dumai waters is also an estuary waters affected by the activities of the land, and the waters that receive input from various types of waste from various activities in Dumai city and surrounding areas. The research was aimed to knowing the general condition of the Dumai sea western waters, analyzing the content of Pb and Cd in sediments, observing the correlation between organic matter and heavy metal of Pb and Cd, and find out the status of pollution Dumai Sea Western Waters by comparing the results of the analysis with some quality standard countries, The method used is a survey method. Based on the Decree of The Minister of Environment No. 51 of 2004, that the general condition of the Dumai sea western waters still can support the life activities of marine organisms in the waters. The results showed that the concentrations of Pb and Cd in sediments of Dumai is below the threshold value. The results of simple linear regression analysis of heavy metals Pb and Cd with organic matter content showed that the concentration of heavy metals Pb and Cd is not influenced by organic matter content or have a very weak correlation with linear regression equation consecutive y = 0,0834x + 7,7866 and y = -0,001x + 0,0559. The status of pollution of Dumai sea western waters for Pb 8,76 µg/g and Cd 0,04 µg/g still under quality standardsKeywords: Dumai Sea Western Waters, Sediments, Heavy Metal Pb and Cd